The Role of the Uleebalang in Aceh's Socio-Political History - Muhammaddar (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
This article aims to look at the role of the Uleebalang in Aceh's socio-political history. The author feels inspired by this research because there is something unique in seeing this elite. They are the pillars of upholding the kingdom of Aceh Darussalam, but on the other hand, they are ordinary people who have many shortcomings in carrying out their roles in society. So it is not uncommon for conflicts to occur between them and the community, even to the point of bloodshed, namely civil war as the climax. This research is felt to be important in order to trace genealogy and find out the problems surrounding it. The very basic problem in this study is the time span of 1900, towards the end of the Aceh war, and the birth of the feudalistic system initiated by the uleebalang, while 1946 was the year the end of the feudalistic period was marked by the outbreak of civil war (Cumbok war) driven by the Ulama. What is at the core of the problem here is how is the position of Uleebalang in the structure of Acehnese society. By using a literature study (library research) and a historical approach, it can be found that the role of the Uleebalang in the socio-political history of Aceh has experienced a shift in status and has experienced ups and downs. This was triggered by several factors including Religion, economics, politics, sociology, and psychology.